Pengaruh Partisipasi Anggaran, Motivasi Dan Disiplin Kerja Terhadap Kinerja Manajerial Di Inspektorat Jenderal Kementerian Perhubungan - Arif Rofi Setiawan; Hidayat Muchtar (Reformasi Administrasi, 2025)
This research is motivated by several things. First, with budget savings, it is feared that it will affect the achievement of targets for the implementation of existing performance indicators. Second, based on the researcher's observations in daily life, the reduction of the budget affects employee motivation. Lastly, based on the researcher's observations in daily life, there is still indiscipline in terms of attendance and completion of reports. This study aims to analyze and evaluate the influence of budget participation, motivation and work discipline on managerial performance at the Inspectorate General of the Ministry of Transportation. This study uses a quantitative research method. The number of samples in this study is all members of the population of 135 respondents so it is called a total sample. The data used is primary data from respondents. The data analysis technique used in this study is multiple linear regression analysis with statistical tests. The results of the study show that there is a partial positive and significant influence of budget participation on managerial performance. Motivation partially showed a positive and significant influence on managerial performance, as well as the discipline variable had a positive influence on managerial performance. Simultaneously there is a positive and significant influence of budget participation, motivation and discipline on managerial performance at the Inspectorate General of the Ministry of Transportation. The Adjusted value of the determination coefficient (Adj R2) of 0.627 means that managerial performance at the Inspectorate General of the Ministry of Transportation can be explained by budget participation, motivation and discipline of 62.7% and the remaining 37.3% explained by other variables outside the research model. So there are several variables that are not researched, for example, budget procedures, leadership, and budget quality.